Sistem Cerdas Berbasis Android Untuk Diagnosa Penyakit Betta Fish (Ikan Cupang) Menggunakan Metode Dempster Shafer - Pane, Deski Helsa; Suryanata, Muhammad Gilang (STMIK Budi Darma, 2022)
This study focuses on designing and making intelligent systems to help diagnose diseases found in betta fish or better known as betta fish using the dempster shafer method, the problem that has been happening is the lack of knowledge of novice cultivators related to the diseases suffered by betta fish resulting in their death. Siamese fighting fish. There are several diseases that often attack betta fish, some of which are Stress, White Spot and Pineapple Scales. In building an android-based intelligent system for diagnosing this betta fish disease, the Research & Development research method is used. The use of the dempster shafer is very suitable to be implemented to diagnose diseases in betta fish (betta fish) which basically users of this application do not know for sure the disease that is being suffered by betta fish